Feldspar mineralogy and rare-earth element (re)mobilization in iron-oxide copper gold systems from South Australia: a nanoscale study - Kontonikas-Charos, Alkis; Ciobanu, Cristiana L.; Cook, Nigel J; Ehrig, Kathy; Ismail, Roniza; Krneta, Sasha; Basak, Animesh (2018)
Nanoscale characterization (TEM on FIB-SEM-prepared foils) was undertaken on feldspars undergoing transformation from early post-magmatic (deuteric) to hydrothermal stages in granites hosting the Olympic Dam Cu-U-Au-Ag deposit, and from the Cu-Au skarn at Hillside within the same iron-oxide copper-gold (IOCG) province, South Australia. These include complex perthitic textures, anomalously Ba-, Fe-, or REE-rich compositions, andREE-flourocarbonate + molybdenite assemblages which pseudomorph pre-existing feldspars. Epitaxial orientations between cryptoperthite (magmatic), patch perthite (dueteric) and replacive albite (hydrothermal) within vein perthite support interface-mediated reactions between pre-existing alkali-feldspars and pervading fluid, irrespective of micro-scale crystal morphology. Such observations are consistent with a coupled dissolution-reprecipitation reaction mechanism, which assists in grain-scale element remobilization via the generation of transient interconnected microporosity. Micro-scale aggregates of hydrothermal hyalophane (Ba-rich K-feldspar), crystallizing within previously albitized areas of andesine, reveal a complex assemblage of calc-silicate, As-bearing fluorapatite and Fe oxides along reaction boundaries in the enclosing albite-sericite assemblage typical of deuteric alteration. Such inclusions are good REE repositories and their presence supports REE remobilization at the grain-scale during early hydrothermal alteration. Iron-metasomatism is recognized by nanoscale maghemite inclusions within ‘red-stained’ orthoclase, as well as by hematite in REE-fluorocarbonates, which reflect broader-scale zonation patterns typical for IOCG systems. Potassium-feldspar from the contact between alkali-granite and skarn at Hillside is characterized by 100–1000 ppm REE, attributable to pervasive nanoscale inclusions of calc-silicates, concentrated along microfractures, or pore-attached. Feldspar replacement by REE-fluorcarbonates at Olympic Dam and nanoscale calc-silicate inclusions in feldspar at Hillside are both strong evidence for the role of feldspars in concentrating REE during intense metasomatism. Differences in mineralogical expression are due to the availability of associated elements. Lattice-scale intergrowths of assemblages indicative of Fe-metasomatism, REE-enrichment and sulfide deposition at Olympic Dam are evidence for a spatial and temporal relationship between these processes.